Analysis of Obstructing Factors for the Implementation of Lean Construction in Hauling Road Construction with A Multiple Linear Regression and Swot Analysis Approach - Dedy Anggara Putra; Budi Susetyo (Green Publisher Indonesia, 2025)
Infrastructure development in the mining sector plays a crucial role in supporting Indonesia's economic growth, with the sector contributing approximately 7–8% of total GDP. However, infrastructure projects face significant challenges related to inefficiency, with more than 40% experiencing delays due to waste and poor resource management. Lean Construction, adapted from Lean Manufacturing principles and introduced by Lauri Koskela in 1993, offers a systematic approach to eliminating waste and enhancing project value. This research aims to analyze the barrier factors affecting Lean Construction implementation in hauling road construction projects and to formulate strategies to overcome these barriers. Using a quantitative approach, this study employed multiple linear regression analysis to examine the relationship between barrier factors (managerial, workforce, organizational, and external factors) and Lean Construction implementation. Data were collected through expert validation and questionnaires from 50 respondents involved in hauling road construction. The results show that these four factors simultaneously influence Lean Construction implementation by 57.7%, with the workforce factor being the most dominant ( ). SWOT analysis identified strategic recommendations, including enhanced Lean Construction training programs with certification, optimization of Lean Tools technology, improved communication systems, and structured organizational commitment. This research contributes to the body of knowledge on Lean Construction implementation in the Indonesian mining infrastructure context and provides practical guidelines for contractors to overcome implementation barriers.